Safety of peripheral intravenous administration of hypertonic saline: a systematic review and meta-analysis - Huang, Sih-Shiang; Sung, Chih-Wei; Huang, Chien-Tai; Hsieh, Mu-Yang; Ko, Jen-Chung; Sheng, Wang-Huei; Huang, Edward Pei-Chuan (Frontiers in Medicine, 2025)
BackgroundHypertonic saline solution is critical for managing symptomatic hyponatremia and increased intracranial pressure (IICP). Though administered via central venous catheters (CVCs) traditionally, peripheral administration is a viable alternative, reducing delays and CVC-associated risks. This review evaluates the safety of peripheral hypertonic saline, focusing on infusion-related adverse events.MethodsA systematic search of MEDLINE, Embase, and Cochrane Library (up to December 2024) identified studies on peripheral hypertonic saline in adults. Studies reporting phlebitis, infiltration, extravasation, and thrombosis were included. Two reviewers independently screened studies and extracted data. Quality was assessed using the Newcastle-Ottawa Scale and Risk of Bias 2 tool. The review is registered on PROSPERO (CRD42024612330).ResultsThirteen studies involving 2,354 patients were included, comprising one randomized controlled trial and 12 cohort studies. Quality assessment showed a low risk of bias across all included studies. The pooled incidence of phlebitis was 2.3% (95% CI: 1.2%−4.1%), while infiltration and extravasation occurred at a rate of 2.1% (95% CI: 1.1%−3.9%). Thrombosis was rare, with an incidence of 0.8% (95% CI: 0.3%−1.7%). Most complications were mild and resolved conservatively.ConclusionPeripheral hypertonic saline is a safe alternative to CVC placement, particularly in urgent situations where rapid intervention is required. Low complication rates support its broader use in clinical practice, enabling timely treatment while minimizing the risks associated with central access. These findings support consideration for updates to clinical guidelines, advocating for peripheral hypertonic saline as a first-line option in appropriate scenarios to enhance patient outcomes and streamline care delivery.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier: CRD42024612330.